Plantlet quality improvement of Paulownia fortunei (Seem.) Hemsl. and Chrysanthemum sp. in vitro via aerated micropropagation - Nhut, Duong Tan; Thien, Nguyen Quoc; Luan, Vu Quoc (Academia Journal of Biology, 2014)
The transplant production using micropropagation techniques has more benefits than that using the seed or the vegetative propagation in terms of genetic uniformity, virus-free or pathogen-free propagules and scheduled production. However, the conventional micropropagation has become costly due to the biological contamination, the morphological disorders and the low photosynthetic capacity of in vitro plantlets. This results in low percent of the survivals ex vitro and requires the acclimatization prior to the ex vitro stage. To overcome this problem, we tried to carry out a new method called aerated micropropagation. The aerated micropropagation of plants using the circular self-adhesive gas permeable membrane (MillisealÒ) was more advantaged than the conventional micropropagation in some culture systems on the growth of Paulownia fortunei (Seem.) Hemsl. and Chrysanthemum sp. We have demonstrated some results presented as below: Jam Vessel (JV) without aeration cap: the fresh weight and plant height of the plantlets in this culture system were smaller than those of plantlets in the JV with aeration cap (one hole). They did not expand their leaves. The plantlets were vitrified because of the high air humidity in the vessels. JV with aeration cap (one hole): the plantlets expanded their leaves widely. Their leaves were so green and large. The growth of the plantlets in these vessels was remarkably greater than that of the plantlets in the closed vessels. The aerated vessels could be used to reduce the air humidity in the vessels. It was a good way to overcome the vitrification in the plantlets cultured in the closed vessels. The aerated micropropagation could be applied as a new useful tool for the micropropagation of Paulownia and Chrysanthemum